Manusia sebagai Subyek dan Obyek dalam Filsafat Eksistensialism Martin Heidegger (Kajian dari Segi Karakteristik dan Pola Pikir yang Dikembangkan) - Nasaiy Aziz (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2013)
Birth of Martin Heidegger's philosophy is caused by reaction about materialism and idealism philosophy opposition. Materialism holds that the human world is only as objects like other objects as a whole. Man according to the form was superior to other objects but essentially is same, as a result of the chemical elements (resultant). While idealism looked just as human as the subject, and finally just as consciousness. Idealism forget that man can only stand as a subject in the face of the object. Humans only stand as a human being as one with the surrounding reality. Unlike with two conflicting streams, existentialism philosophy sees humans as subjects and objects at once, not just one of them.